2010
DOI: 10.1007/s10549-010-0998-5
|View full text |Cite
|
Sign up to set email alerts
|

Triple negative breast cancer in Korea-distinct biology with different impact of prognostic factors on survival

Abstract: We analyzed breast cancer subtypes using Korean Breast Cancer Society Registration Program data to compare clinical features and prognosis for triple-negative breast cancer (TNBC). A cohort of 26,767 breast cancer patients were divided in four groups: luminal A (ER+ and/or PR+, HER2-), luminal B (ER+ and/or PR+ HER2+), HER2+ (ER-, PR-, HER2+), and triple-negative (ER-, PR-, HER2-). Clinicopathologic factors were evaluated. The luminal A (14,437 patients, 53.9%) subtype was the largest in our study. Compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
43
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 37 publications
9
43
2
Order By: Relevance
“…Triple-negative breast cancer has been widely studied and advocated in several studies (16,17) to have a poor prognosis among the various breast cancer subtypes. In contrast, there is limited data on triple-positive breast cancer in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triple-negative breast cancer has been widely studied and advocated in several studies (16,17) to have a poor prognosis among the various breast cancer subtypes. In contrast, there is limited data on triple-positive breast cancer in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there is limited data on triple-positive breast cancer in the literature. Although patients with triple-positive breast cancer may benefit from the use of hormonal therapy and immunotherapy -unlike patients with triple-negative breast cancer -triple-positive breast cancer is often not reported as the subtype with the best survival, (16,17) and its survival rate remains unpredictable. Therefore, a prognostic biomarker for triple-positive breast cancer is imperative.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other breast cancer patients, the average age of this group is lower and includes more pre-menopause cases (14)(15)(16)(17)(18)(19). However, one study by Iwase reported that triple negative patients were more frequently postmenopausal (16).…”
Section: Discussionmentioning
confidence: 99%
“…However, one study by Iwase reported that triple negative patients were more frequently postmenopausal (16). Numerous studies indicated that in comparison with other cases, pathological grade of TNTs were higher (13,17,(20)(21)(22)(23) and Ki67 over expression was more common (8,9,14,20,21). In a retrospective cohort study on Korean breast cancer society registration program data, TNBC patients showed higher tumor size, lymphatic stage, histological grade, and more lymphovascular invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Yin and colleagues suggested that the biological behavior and clinical outcome for TNC in Chinese patients may be more favorable than those in Western populations. On the other hand, population-based study from Korea (Lee et al, 2010) commented that it was too early to conclude that clinicopathological features in Asians were unique. In view of paucity of data in Chinese and Asians, we carried out a cohort study on Hong Kong Chinese women with TNC patients.…”
Section: Introductionmentioning
confidence: 99%